Early onset of cardiomyopathy and intellectual disability in a girl with Danon disease associated with a de novo novel mutation of the LAMP2 gene. Issue 6 (5th May 2016) - Sugie, Kazuma; Yoshizawa, Hiroyuki; Onoue, Kenji; Nakanishi, Yoko; Eura, Nobuyuki; Ogawa, Megumu; Nakano, Tomoya; Sakaguchi, Yasuhiro; Hayashi, Yukiko K.; Kishimoto, Toshifumi; Shima, Midori; Saito, Yoshihiko; et al.
Abstract : Danon disease, primary lysosome‐associated membrane protein‐2 (LAMP‐2) deficiency, is characterized clinically by cardiomyopathy, myopathy and intellectual disability in boys. Because Danon disease is inherited in an X‐linked dominant fashion, males are more severely affected than females, who usually have only cardiomyopathy without myopathy or intellectual disability; moreover, the onset of symptoms in females is usually in adulthood. We describe a girl with Danon disease who presented with hypertrophic cardiomyopathy and Wolff‐Parkinson‐White (WPW) syndrome at 12 years of age. Subsequently, she showed signs of mild learning disability and intellectual disability on psychological examinations. She had a de novo novel mutation in the LAMP‐2 gene and harbored an identical c.749C > A (p.Ser250X) variant, resulting in a stop codon in exon 6. She showed decreased, but not completely absent LAMP‐2 expression on immunohistochemical and Western blot analyses of a skeletal muscle biopsy specimen, which has been suggested to be caused by a 50% reduction in LAMP‐2 expression (LAMP‐2 haploinsufficiency) in female patients with Danon disease caused by a heterozygous null mutation. To our knowledge, our patient is one of the youngest female patients to have been given a diagnosis of Danon disease. In addition, this is the first documented case in a girl that was clearly associated with intellectual disability, which is very rare in females with Danon disease. Our findings suggest that studies of female patients with Danon disease can extend our understanding of the clinical features of this rare disease.